1996
DOI: 10.1038/ng0996-62
|View full text |Cite
|
Sign up to set email alerts
|

Sox9 expression during gonadal development implies a conserved role for the gene in testis differentiation in mammals and birds

Abstract: Heterozygous mutations in SOX9 lead to a human dwarfism syndrome, Campomelic dysplasia. Consistent with a role in sex determination, we find that Sox9 expression closely follows differentiation of Sertoli cells in the mouse testis, in experimental sex reversal when fetal ovaries are grafted to adult kidneys and in the chick where there is no evidence for a Sry gene. Our results imply that Sox9 plays an essential role in sex determination, possibly immediately downstream of Sry in mammals, and that it functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
185
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 723 publications
(200 citation statements)
references
References 53 publications
8
185
0
1
Order By: Relevance
“…The expression of Sox9 at high levels in Sertoli cells also favors the hypothesis that additional proteins are needed to differentiate the phenotype of chondrocytes from that of Sertoli cells (20,21). Hence, the purpose of the present study was to further identify sequences in the Col2a1 48-bp enhancer essential for its chondrocyte-specific activity and to determine whether chondrocyte-specific nuclear proteins bound to these sequences.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…The expression of Sox9 at high levels in Sertoli cells also favors the hypothesis that additional proteins are needed to differentiate the phenotype of chondrocytes from that of Sertoli cells (20,21). Hence, the purpose of the present study was to further identify sequences in the Col2a1 48-bp enhancer essential for its chondrocyte-specific activity and to determine whether chondrocyte-specific nuclear proteins bound to these sequences.…”
mentioning
confidence: 78%
“…In situ hybridization during mouse embryogenesis showed that Sox9 is expressed in all chondroprogenitor cells; Sox9 expression generally parallels that of Col2a1 even in some non-chondrocytic cells and increases together with that of Col2a1 when frank chondrocyte differentiation takes place (5,18,19). The expression of Sox9 in gonadal ridges and later in the Sertoli cells of the testis presumably accounts for the sex reversal in CD patients (20,21). Overall, the abnormal skeletal manifestations of CD patients and the pattern of expression of Sox9 during embryonic development suggest that Sox9 plays an important role in the pathway of chondrocyte differentiation.…”
mentioning
confidence: 99%
“…3). Sex reversal was not observed in the AMH-NICD1 model, because the levels of Sox9, 84,85 Dax1, 86 and Foxl2 87 expression in Sertoli cells were not significantly altered in our microarray (GSE37073).…”
Section: Phenotype Of Sertoli Cells In Wild-type and Amh-nicd1 Testesmentioning
confidence: 99%
“…These include SOX9, a highly conserved HMG domain transcription factor that is implicated in testis development across all groups from fish to reptiles, birds and mammals (Morais da Silva et al 1996. In female embryos of egg-laying species such as birds and reptiles, estrogen is required for proper ovary formation, and testis-enriched DMRT1 can antagonise estrogen production (Elbrecht & Smith 1992, Yao et al 2004, Lambeth et al 2014.…”
Section: Sex Determination and Testis Development In Non-mammalian Vementioning
confidence: 99%